2020
DOI: 10.4103/jfmpc.jfmpc_351_20
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of red cell alloimmunization in multi transfused patients at a Tertiary care teaching hospital

Abstract: Background: Red blood cell (RBC) alloimmunization is an immune response against foreign RBC antigens; this generally occurs after sensitization due to multiple blood transfusions and pregnancies. Antibody detection plays a critical role in transfusion medicine as it can detect irregular or unexpected antibodies. This study was done to know the frequency and specificity of unexpected red cell antibodies in the multitransfused patients. Materials and Methods: This prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the study by Anjali Handa et. al, anti-K was most common allo-antibody (42.8%) followed by anti E (28.57%) [10] . Dhawan et al and Roopam et al also found similar results, where anti-K was more frequent [11,12] .…”
Section: Resultsmentioning
confidence: 94%
“…In the study by Anjali Handa et. al, anti-K was most common allo-antibody (42.8%) followed by anti E (28.57%) [10] . Dhawan et al and Roopam et al also found similar results, where anti-K was more frequent [11,12] .…”
Section: Resultsmentioning
confidence: 94%
“…It has been explicitly shown that the antibodies to Rh-K and MNS blood group antigens are among the commonly reported specificities in these studies. 6 , 7 , 8 Only a few studies (predominantly from the northern and western parts of the country) have reported the frequencies of clinically significant antigens among their donor population. 9 - 14 As shown in the present study, the R1R1 and R1r (among D+ donors) and rr (among the D- donors) were found to be the most frequent Rh antigen phenotypes in virtually all the studies conducted in India.…”
Section: Discussionmentioning
confidence: 99%
“…Most RBC alloantibodies may lead to serious or fatal clinical consequences, including acute or delayed haemolytic reactions, anaemia and haemolytic disease of the newborn [1,3]. The incidence of RBC alloimmunization after blood transfusion is the most reported at present and different studies with specific populations have come to different conclusions, with data between 1% and 10% [4][5][6].…”
Section: Introductionmentioning
confidence: 99%